Removing acid mist in flue gas emissions: article / Muhammad Firdaus Salehon and Safari Zainal - Salehon, Muhammad Firdaus; Zainal, Safari (2017)
Air pollution can be very harmful to human or biodiversity. In order to overcome this problem, this study has been conducted which aiming to study the removal hydrobromic acid by using NaOH solution and to investigate the effect of concentration of NaOH toward acid gas. This research will be focused on removing acid mist which is hydrogen bromide acid. Major acid removal is by using the scrubbing method. This study performed a gas chromatography analysis to tracing the compound in the gas sample. Hydrobromic acid mist will be remove by using 1M, 2M and 3M concentration of NaOH and different time contact which 10min, 20min and 30min each concentration. Based on the analysis higher concentration of NaOH will removed higher content of hydrogen bromide gas mist. For removal of hydrogen bromide using 1M NaOH solution after 30 min the percent of reduction is 75.6%. secondly for removal using 2M NaOH the results shows percent of reduction after 30min is 84.7%. lastly for the 3M NaOH remove 89.1%. Based on the data, it shows that 3M of NaOH with the longer contact times which is 30min can’t remove 100% of Hbr acid mist, so its required higher concentration of NaOH solution.